(n-5)(n-6)(n-7)=360

Simple and best practice solution for (n-5)(n-6)(n-7)=360 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n-5)(n-6)(n-7)=360 equation:



(n-5)(n-6)(n-7)=360
We move all terms to the left:
(n-5)(n-6)(n-7)-(360)=0
We multiply parentheses ..
(+n^2-6n-5n+30)(n-7)-360=0
We move all terms containing n to the left, all other terms to the right
(+n^2-6n-5n+30)(n-7)=360

See similar equations:

| 2*8+12*4=14+10x | | 45/5+9x=18 | | 3i+6=7(1-2) | | 22-3x=x+6 | | 18+7-x=12-112 | | 900x=1800 | | 101+58+58=x | | 9.t=81 | | 101-58=x | | 99/9*2=27x | | 9k+21=-33 | | 101+58=x | | (4x+16)+(7x-1)=180 | | 4x+3=15–2x | | 3r+2–r=-4 | | (0.5)^3x+2=8^(5x-4) | | –8−3n=10−5n | | (2x-39)°(3x+14)= | | 2x+12=88 | | x^2+23=123 | | 2f+13=-11 | | 130+40=y | | x/5+x+1/3=2 | | –5c=–8c+9 | | 7x-13=4x= | | 7-20x*4=-128+27 | | h-(-13.94)=21.06 | | 36+63=y | | 3.6d=2.7 | | 25-6a=7 | | x+18.99=14 | | 34-y/2=-12 |

Equations solver categories